2017
DOI: 10.1504/ijnt.2017.082455
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of magnetic nanoparticles by low-energy dual ion implantation of iron and nickel into silicon dioxide followed by electron beam annealing

Abstract: Magnetic nanoparticles have been made by low-energy dual ion implantation of iron and nickel into SiO 2 with a nickel fluence ratio of 82% followed by electron beam annealing for 1800 s at 1000°C. After annealing, there is significant diffusion of iron and nickel into the silicon dioxide layer. Annealing also led to the formation of superparamagnetic nanoparticles with a narrow particle size distribution. The saturation moment at 5 K was 0.7 µ B

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It was also shown that Ni + implantation followed by annealing leads to formation of magnetic nanoparticles e.g. in silicon [22], SiO 2 [23] or ZnO [24]. A similar combination of Ni + implantation and annealing enables change of optical properties of sapphire [25].…”
Section: Introductionmentioning
confidence: 96%
“…It was also shown that Ni + implantation followed by annealing leads to formation of magnetic nanoparticles e.g. in silicon [22], SiO 2 [23] or ZnO [24]. A similar combination of Ni + implantation and annealing enables change of optical properties of sapphire [25].…”
Section: Introductionmentioning
confidence: 96%